IUS CONSTITUENDUM: REGULATION OF TRADITIONAL CULTURAL EXPRESSIONS WITHIN THE FRAMEWORK OF THE INTELLECTUAL PROPERTY RIGHTS REGIME AS A STRENGTHENER OF NATIONAL IDENTITY - Maddusila, Sitti Fatimah (Pena Justisia: Media Komunikasi dan Kajian Hukum, 2024)
Indonesia is rich in diverse traditional cultural expressions that need to be protected from misuse or irresponsible commercialization. Efforts to safeguard these cultural expressions can be undertaken by integrating them into the Intellectual Property Rights (IPR) regime through comprehensive and effective legal regulations. The aim of this research is to formulate an ideal concept for regulating traditional cultural expressions within the IPR regime as a means to strengthen national identity in Indonesia, and to identify challenges and obstacles in integrating the protection of traditional cultural expressions into the IPR regime. This research employs normative legal research methods with legislative and conceptual approaches. The legal materials used include primary, secondary, and tertiary legal sources, with data collection techniques through literature study and qualitative data analysis. The research results indicate that the ideal concept for regulating traditional cultural expressions within the IPR regime to strengthen national identity in Indonesia must include a clear definition of traditional cultural expressions and their criteria, the establishment of a comprehensive data and inventory system, provision of legal protection and management mechanisms involving the community owners, assurance of fair profit-sharing in case of commercial utilization, regulation of government and community roles in preservation, and the reinforcement of national identity by recognizing traditional cultural expressions as protected and promoted national assets. The main challenges and obstacles include the absence of clear definitions and criteria, issues of communal ownership, the diversity of cultural expressions, the need to balance protection and access for utilization, lack of community capacity and awareness, and limitations in resources and supporting infrastructure.